The Identification of Teachers’ Ability of the Fourth Grade Students in Implementing Thematic Learning in Curriculum 2013 in SD N. 4 Banyuasri - Kadek Ashadi Putra (Journal of Psychology and Instruction, 2017)
This study was conducted to identify the ability of IV grade teacher of implementation of Curriculum 2013 in SD No. 4 Banyuasri in the academic year of 2013/2014 viewed from lesson planning, learning implementation, and learning assessment implementation. This study included as a qualitative descriptive study. The subjects of this study were thematic teachers at SD No. 4 Banyuasri, lesson planning, and assessment paper. The objects of this study were teacher’s ability of implementation of Curriculum 2013 in SD No. 4 Banyuasri viewed from lesson planning, learning implementation, and learning assessment implementation. The data collecting method of this study were observation, interview, and documentation. The obtained data were in the form of qualitative data (interview transcript and documentation) also of value variables of lesson planning, learning implementation, and learning assessment implementation. The data were analyzed by statistic descriptively. The result of analysis showed that the lesson planning who designing by IV grade Thematic teachers at SD No. 4 Banyuasri was qualified very good with an average value of 24 (of maximal total value 24). Learning implementation was qualified good with an average value of 51 (of maximal total value 68). The learning assessment implementation was qualified good with an average value of 11 (of maximal total value 16).